(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2025)
This article explores the role of adults, especially the mother, in the formation of a child’s psyche during infancy, as well as the importance of emotional communication and the negative effects of its deficiency (emotional deprivation) on a child’s mental health. The issue is also analyzed based on the scientific views and research findings of psychologists.